Pregunta
upstudy study bank question image url

(d) Suppose that a cell dehydration model satisfies the differential equation, \[ \frac{d W}{d t}=-k W^{\frac{2}{3}} \] Assume that the volume of water in the cell initially is \( W(0)=8 \mathrm{~mm}^{3} \). Also, assume that the volume of water has decreased to \( W(6)=1 \mathrm{~mm}^{3} \) after 6 hours. (i) Solve the differential equation by separating like variables. (ii) Determine the value of k and the time when the cell will be completely dry.

Ask by Park West. in South Africa
Feb 03,2025

Solución de tutoría real

Respuesta verificada por el tutor

Responder

The solution to the differential equation is: \[ W(t) = \left(\frac{6 - k t}{3}\right)^3 \quad \text{mm}^3 \]

Solución

### Problem (d)(i): Solving the Differential Equation by Separating Variables We are given the differential equation governing the volume of water \( W(t) \) in a cell: \[ \frac{dW}{dt} = -k W^{\frac{2}{3}} \] with the initial condition \( W(0) = 8 \, \text{mm}^3 \). **Step 1: Separate Variables** To solve the differential equation, we separate the variables \( W \) and \( t \): \[ \frac{dW}{W^{\frac{2}{3}}} = -k \, dt \] **Step 2: Integrate Both Sides** Next, we integrate both sides of the equation: \[ \int W^{-\frac{2}{3}} \, dW = \int -k \, dt \] **Integral on the Left Side:** \[ \int W^{-\frac{2}{3}} \, dW = \frac{3}{1} W^{\frac{1}{3}} + C_1 = 3 W^{\frac{1}{3}} + C_1 \] **Integral on the Right Side:** \[ \int -k \, dt = -k t + C_2 \] Combining both integrals: \[ 3 W^{\frac{1}{3}} + C_1 = -k t + C_2 \] For simplicity, let \( C = C_2 - C_1 \): \[ 3 W^{\frac{1}{3}} = -k t + C \] **Step 3: Apply Initial Condition** Using the initial condition \( W(0) = 8 \, \text{mm}^3 \): \[ 3 (8)^{\frac{1}{3}} = 3 \times 2 = 6 = -k \times 0 + C \implies C = 6 \] **Step 4: Solve for \( W(t) \)** Substituting \( C = 6 \) into the equation: \[ 3 W^{\frac{1}{3}} = 6 - k t \] Divide both sides by 3: \[ W^{\frac{1}{3}} = \frac{6 - k t}{3} = 2 - \frac{k t}{3} \] Cubing both sides to solve for \( W(t) \): \[ W(t) = \left(2 - \frac{k t}{3}\right)^3 \] **Final Solution:** \[ W(t) = \left(2 - \frac{k t}{3}\right)^3 \quad \text{mm}^3 \] Alternatively, it can be written as: \[ W(t) = \left(\frac{6 - k t}{3}\right)^3 \quad \text{mm}^3 \] Both forms are equivalent and valid representations of the solution. ### Answer Problem i Answer: After separating and integrating, a general solution is  W(t) = [(6 – k t) ⁄ 3]³. Thus,  W(t) = ((6 − kt)/3)^3 mm³.

Revisado y aprobado por el equipo de tutoría de UpStudy

error msg
Explicar
Simplifique esta solución

Beyond the Answer

To solve the differential equation \[ \frac{d W}{d t} = -k W^{\frac{2}{3}}, \] we will begin by separating the variables. This involves rearranging the equation to isolate \( W \) and \( t \) on opposite sides: \[ \frac{d W}{W^{\frac{2}{3}}} = -k dt. \] Next, we integrate both sides. The left side will be integrated with respect to \( W \), and the right side with respect to \( t \): \[ \int W^{-\frac{2}{3}} dW = \int -k dt. \] The left integral evaluates to: \[ \frac{W^{\frac{1}{3}}}{\frac{1}{3}} = 3W^{\frac{1}{3}} + C_1, \] and the right evaluates to: \[ -k t + C_2. \] Setting both results equal gives us: \[ 3W^{\frac{1}{3}} = -kt + C. \] Now let's solve for \( W \) from the equation above: \[ W^{\frac{1}{3}} = \frac{-kt + C}{3}. \] Cubing both sides, we find \[ W = \left(\frac{-kt + C}{3}\right)^{3}. \] Next, we need to find the constants using the initial conditions provided: \( W(0) = 8 \) and \( W(6) = 1 \). Using the first condition, we input \( t = 0 \): \[ 8 = \left(\frac{C}{3}\right)^3. \] So, \[ C = 3 \cdot 8^{\frac{1}{3}} = 3 \cdot 2 = 6. \] Next, we use the second condition \( W(6) = 1 \): \[ 1 = \left(\frac{-6k + 6}{3}\right)^{3}. \] Taking the cube root gives: \[ 1 = \frac{-6k + 6}{3} \Rightarrow -6k + 6 = 3 \Rightarrow -6k = -3 \Rightarrow k = \frac{1}{2}. \] With \( k \) found, our expression for \( W \) becomes: \[ W = \left(\frac{-\frac{1}{2} t + 6}{3}\right)^{3}. \] To find when the cell will be completely dry, we set \( W = 0 \): \[ \frac{-\frac{1}{2} t + 6}{3} = 0 \Rightarrow -\frac{1}{2} t + 6 = 0 \Rightarrow t = 12. \] Thus, the cell will be dry after 12 hours. In summary: (i) Solution is \[ W = \left(\frac{-\frac{1}{2} t + 6}{3}\right)^{3}. \] (ii) Value of \( k \) is \( \frac{1}{2} \), and the cell will be completely dry at \( t = 12 \) hours.

preguntas relacionadas

Latest Calculus Questions

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad